Stress and polycystic ovarian morphology in functional hypothalamic amenorrhea: a retrospective cohort study - Marlene Hager; Didier Dewailly; Rodrig Marculescu; Stefan Ghobrial; John Preston Parry; Johannes Ott (BMC, 2023)
Abstract Background Women with functional hypothalamic amenorrhea (FHA) reveal polycystic ovarian morphology (PCOM) in up to 50%. If stress sensitivity in women with polycystic ovary syndrome (PCOS) is the reason why PCOS women are prone to develop FHA, patients with FHA caused by stress should reveal PCOM more often. Methods In a retrospective cohort study, 38 stress-associated and 38 excessive exercise-induced FHA women were included. The main outcome parameter was PCOM. In addition, the focus was on general patient characteristics as well as on prolactin, dehydroepiandrosterone-sulphate (DHEAS), and anti-Mullerian hormone (AMH). Results PCOM was found in 34/76 patients (44.7%). The stress group showed a higher prevalence of PCOM than the excessive exercise group (57.9% versus 31.6%, p = 0.019) as well as higher prolactin levels (median 13.2ng/mL versus 11.7ng/mL, p = 0.008) and a trend towards higher DHEAS levels (p = 0.058). Conclusions In FHA women, the PCOM prevalence was significantly higher in the stress-group than in the excessive exercise-group. The well-known stress sensitivity in women with PCOS might explain why PCOS women are prone to develop FHA as well as the high PCOM prevalence in FHA women.